The Great War of Enclosure: Securing the Skies. Issue 4 (25th January 2017) - Shaw, Ian G.R.
Abstract: Swarms of police drones, fleets of overhead delivery bots, and flocks of private security drones are set to multiply the complex interfaces between state, capital, and sense. This paper explores the military and economic enclosure of the atmosphere by drones. For centuries, capitalist enclosure has privatized and secured common spaces: territorializing new power relations into the soil. Enclosure now operates through an increasingly atmospheric spatiality . The birth of airpower enabled new vertical regimes of state power, capital accumulation, and violence. Now, drones are materializing both intimate and pervasive colonizations of local, national, and international airspace. Crucially, this discloses new morphologies and ontologies of urban (in)security, in which an atmospheric state polices deterritorialized aerial circulations. Such a reenchanted atmosphere collapses the geopolitical and geoeconomic in uncertain robotic orbits. This paper, which connects past and present, is driven by a deeper concern for the existential dimensions of dronified skyscapes, subjects, and violence.